Pola Komunikasi Interpersonal Pendamping Sosial dalam Menangani Anak Bermasalah Hukum (ABH) di Kabupaten Madiun - Romli Romli; Latutik Mukhlisin; Anwar Soleh Azzarkoni (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2024)
Children in Conflict with the Law (CICL) are highly vulnerable to rights violations and developmental disruptions due to the pressures of adapting to judicial processes. In such circumstances, CICL require support from companions who can provide assistance beyond the roles of parents or immediate family. This study aims to analyze the interpersonal communication patterns employed by social workers in Madiun Regency when assisting CICL. Referring to Joseph A. Devito's theory of interpersonal communication, this research examines the application of five core principles: openness, equality, empathy, supportiveness, and positiveness. This study adopts a qualitative approach with a case study method. Data were collected through observations, interviews, and documentation. The findings reveal that the interpersonal communication patterns employed by social workers have a significant positive impact on CICL under the coordination of the Social Services Department of Madiun Regency. CICL feel supported in expressing their grievances (openness) due to the empathy and patience (empathy) demonstrated by the social workers. The social workers also successfully foster an atmosphere of equality by deeply understanding the conditions and feelings of the CICL. The supportiveness provided by the social workers not only ensures a sense of security but also builds the self-confidence of CICL, encouraging them to adopt more positive attitudes (positiveness). Some CICL who were initially reluctant to communicate eventually felt comfortable opening up and actively discussing their problems.